Recent advances in the structure and immunomodulatory activity of food-derived glycoprotein complex - Yu Zhong; Jiangxiong Zhu; Bifen Zhu; Hao Yin; Danfeng Wang; Yun Deng; Minyan Zhang; Chunrong Zhang (Journal of Future Foods)
Glycoprotein complexes, a kind of structural biomolecules, are characterized by extensive functions, such as immunomodulatory and anti-inflammatory activities. Glycosylation of protein has an important impact on conformational stability and active function of glycoprotein complex. Clarifying the structure of glycoprotein complex is the basis for further exploring its biological activities, and the release of sugar chains is one of the key points in the analysis of glycoprotein structures. Glycoprotein complex can affect the expression of immune-related proteins and factors by activating cell surface receptors, regulating intracellular immune signal transduction, and ultimately play an immunomodulatory role in the body. Meanwhile, the chemical structure and advanced structure of glycoprotein complex can significantly affect the immunomodulatory activity. This review focuses on chemical and advanced structural information of glycoprotein, the regulation mechanism of immunomodulation and the structure-activity relationship, which aims to provide a theoretical basis for the basic research on the immunomodulatory activity of food-derived glycoproteins and the development of related functional products.